‎802.11 Basic Concepts and Mechanisms for ‎Network Building Management System (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This research aims at providing the reader with a demonstration of the very standards for wireless networks. We all know IEEE 802.11 and types of scale but what are the differences between the technical and privileges diverse flavors? What is meant by "technically" that level as ten times faster than the level p? Not only cover the creation of this research on the IEEE 802.11 wireless networking standards the most comprehensive, but also pave the modern standard for broadband wireless IEEE 802.11 (Wi-Fi). This paper presents also a trade-off between different technology standards in terms of the extent of coverage, the possibility of expanding the service feature in order to help accommodate the fundamental disparity between these term IEEE 802.11 (LAN RF) family of standards for networks .difference between IEEE 802.11 base modifications (a/b/g, etc.) in the coding techniques, frequency range and change for the best made the original style of approach to the IEEE 802.11 standard layout (Wi-Fi) is intended to be a solution with large cells rapid foreign networks, while Wi-Fi standard plans (802.11 ) is intended to be a solution for networks operating within the buildings based on the few cells